Neuroaesthetics A Methods-Based Introduction - Balinisteanu, Tudor; Priest, Kerry (Springer Nature, 2024)
​This open access neuroaesthetics textbook, the first in the world, is designed for teaching a semester module (14 meetings) to undergraduate/masters students from both the sciences and the humanities. Written in a style that appeals to humanities students without prior science training, and to science students without prior humanities training, the textbook contains 6 Units, material for an introductory class, and summative comments to be discussed in a closing meeting. Each Unit comprises an overview designed as student home reading, a lecture, and a lab. The labs contain detailed step-by-step instructions for running a basic experiment and analysing the collected data, that can be easily implemented in humanities and science departments alike. The textbook introduces students to philosophical considerations of neuroaesthetics topics in context of the history of empirical aesthetics, showcases experimental approaches to the empirical study of dance, the visual arts, and music, and supports hands-on training in experimental research methods.